2000
DOI: 10.1074/jbc.m908297199
|View full text |Cite
|
Sign up to set email alerts
|

IB1 Reduces Cytokine-induced Apoptosis of Insulin-secreting Cells

Abstract: IB1/JIP-1 are recently characterized mammalian scaffold proteins involved in the regulation of the JNK 1 signaling pathway (1-3). These two isoforms bind to and associate in a single transduction complex three kinases, MLK3, MKK7, and JNK, which together constitute an ordered unit of sequential signaling molecules transducing a variety of stress signals (2, 3). To date, five different isoforms of the protein have been cloned, which are mainly N-terminal splice variants that arise from expression of one single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
109
2
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(120 citation statements)
references
References 42 publications
6
109
2
3
Order By: Relevance
“…26 It has been also reported that JNK activation is increased following transient global focal ischaemia, in particular in the CA1 neurons of the hippocampus. 27 In other cell systems, IB1/JIP-1 was shown to be downregulated once cells were exposed to various stresses such as UV, cytokines, parietal stress or starving 10,28 . As a consequence, JNK activity is increased and the cells undergo a pro-apoptotic pathway.…”
Section: Introductionmentioning
confidence: 99%
“…26 It has been also reported that JNK activation is increased following transient global focal ischaemia, in particular in the CA1 neurons of the hippocampus. 27 In other cell systems, IB1/JIP-1 was shown to be downregulated once cells were exposed to various stresses such as UV, cytokines, parietal stress or starving 10,28 . As a consequence, JNK activity is increased and the cells undergo a pro-apoptotic pathway.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that beta cell destruction by cytokines such as IL-1β [34,35] can be prevented by inhibition of the JNK pathway [24,36], implying that JNK plays a role in the autoimmune beta cell destruction found in the early stage of type 1 diabetes. In addition, the JNK pathway is activated in various tissues, including pancreatic islets, in the diabetic state, and suppression of that pathway reduces insulin resistance and ameliorates glucose intolerance in type 2 diabetic animal models [37].…”
Section: Discussionmentioning
confidence: 99%
“…57,58 MAPK8IP1 Mitogen-activated protein kinase 8 interacting protein 1 MAPK8IP1 is a regulator of pancreatic beta-cell function and has been shown to prevent MAPK8-mediated activation of transcription factors, and decrease IL-1 beta and MAP kinase 1 (MEKK1)-induced apoptosis in pancreatic beta cells. 59 MAPK8IP1 has also been shown to be a DNA-binding transactivator of the glucose transporter GLUT2, and mutations in MAPK8IP1 have been shown to be associated with type 2 diabetes. 60 MAPK8IP1À/À mice die before blastocyst implantation suggesting that it is required for early embryogenesis in mice.…”
Section: Cry2mentioning
confidence: 99%